Simulated hair and preparation method thereof

Through the blending technology of polyvinyl alcohol, protein and carboxylated graphene oxide, combined with wet spinning and glycerin treatment, the shortcomings of synthetic fiber hair in flame retardant properties, fluffyness and safety were solved, and high preparation was achieved The strong and flexible regenerated protein fibers realize the market application prospects of simulated hair.

CN119265747APending Publication Date: 2025-01-07SHAOXING YUAN NON-WOVEN CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411470764.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing synthetic fiber hairs have shortcomings in flame retardant properties, fluffiness, production costs and safety, and often lead to skin burns and allergic reactions.

Method used

Polyvinyl alcohol, protein, and carboxylated graphene oxide nanoreinforced materials were used to blend the filament to prepare regenerated protein fibers, combined with wet spinning process, and glycerol and antibacterial agents were added to improve the flexibility and mechanical properties of the fibres.

Benefits of technology

It solves the problems of distortion, strength and modulus of traditional fibers, and prepares simulated hair with smooth and smooth surface, excellent strength and heat resistance. It has a simple process, economical, green and environmentally friendly, suitable for continuous industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides simulated hair and a preparation method thereof.The method takes polyvinyl alcohol and soybean protein as raw materials, the simulated hair is prepared through blending and wet spinning, and the method comprises the following steps that 1, the polyvinyl alcohol and the soybean protein are dissolved into a solution with a certain concentration, and then the polyvinyl alcohol and the soybean protein are mixed according to a certain proportion to form a mixture; nano particles, a cross-linking agent, a flame retardant, an antibacterial agent and the like are added and blended into a spinning solution; (2) standing and defoaming the spinning solution, then preparing nascent fibers through wet spinning, and obtaining the polyvinyl alcohol / protein cellosilk through post-treatment procedures such as hot stretching and shaping, acetalation, washing and drying. The composite fiber material for the wig, provided by the invention, is wide in raw material source, green and environment-friendly, relatively low in cost, soft and smooth in hand feeling and excellent in strength and modulus; the flame retardant property is relatively good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of chemical fiber materials, and in particular to simulated hair and a preparation method thereof. Background Art

[0002] Hair products are wigs made of human hair or special chemical fibers through a series of processes. They can be divided into springs, wigs, hair pieces, and accessories. According to the material, they can be divided into human hair products, chemical fiber products, and mixed products of human hair and chemical fiber. They are mainly used for hair styling, beauty and hairdressing teaching, and to make up for physiological defects such as hair loss and hair loss, and to meet the needs of special professions (such as performing arts, lawyers, etc.). Among them, the vast majority of products are used for hair styling, and have the characteristics of quasi-necessities and fashionable consumption.

[0003] At present, the materials for preparing wig fibers are mainly derived from synthetic fibers, including polyvinyl chloride (PVC) fibers, polyethylene terephthalate (PET) fibers, polyacrylonitrile (PAN) fibers, etc. Chinese invention patent CN112680810B adds heat stabilizers, lubricants and other substances to PVC resin to prepare a PVC fiber composition for simulated wigs with soft gloss and smooth feel; Chinese invention patent CN115369515A mixes silver-loaded bentonite antibacterial agent with modified polyester resin, and prepares an antibacterial wig by melt spinning after extrusion granulation; Chinese invention patent CN113774519B mixes oleic acid-modified fluorine-doped nano-titanium dioxide, modified polyethylene terephthalate-1,4-cyclohexane dimethanol ester (PETG), neopentyl glycol and other substances with polyethylene terephthalate to prepare a wig with good gloss and smooth surface. Chinese invention patent CN114592346A discloses a comfortable hemp fiber wig made by pre-treating hemp fiber and finishing it with ionic liquid. Chinese invention patent CN110331463A adds porous polymer filler powder, nanographene and other substances to polyacrylonitrile, and prepares a foamed synthetic fiber with good air permeability and heat dissipation through solution spinning.

[0004] In the applicant's search scope, PVC wig fibers have good natural flame retardancy and curling properties, but poor fluffiness; PET wig fibers have high modulus, high strength and excellent heat resistance, but poor flame retardancy; PAN wig fibers have a natural appearance and good flame retardancy, and are often used to prepare high-end wig products, but the production cost is high, the market price is high, and the glossiness is too high. The main disadvantages are the large amount of chemical modifiers, high pollution, and complex preparation process. These synthetic fibers will produce heat melting when burned, causing skin burns, and they are prone to skin allergies due to static electricity irritation when worn. Summary of the invention

[0005] In view of the above shortcomings of synthetic fiber hair, this experiment uses protein with a wide range of sources, low price, and green environmental protection, polyvinyl alcohol (PVA) with high strength, wear resistance, and corrosion resistance, as well as carboxylated graphene oxide nano-reinforced materials with UV resistance, pollution resistance, excellent mechanical properties, and black color for blending and spinning. The obtained regenerated protein fiber effectively solves the problems of distortion and unsmoothness of traditional chemical fiber hair; low strength and modulus of natural polymer fiber hair. The preparation process of the present invention is simple, economical, green and environmentally friendly, easy to implement in continuous industrial production, and has broad market application prospects. The simulated hair of the present invention is composed of the following components (the contents of the components involved in the present invention are all mass percentages): polyvinyl alcohol 60-90%, protein 5-40%, cross-linking agent 0.2-1%, flame retardant 0.8-2%, antibacterial agent 0.1-1% and 0.1%-1% carboxylated graphene oxide, and the total amount of each component is 100%. Polyvinyl alcohol is selected from products with high alcoholysis degree of polymerization of more than 1700, such as 1799 type, 2199 type, 2499 type, etc. The protein is soy protein, keratin, milk protein, and silk protein.

[0006] To this end, the technical solution of the present invention is as follows: A simulated hair and a preparation method thereof, wherein the specific preparation process comprises the following steps: Step 1 Preparation of spinning solution: (1) Washing of polyvinyl alcohol: Place polyvinyl alcohol in a certain amount of water and stir at room temperature for 1 to 2 hours to remove impurities such as sodium acetate and oligomers; (2) Dissolution of polyvinyl alcohol: Mix the washed polyvinyl alcohol with distilled water in a certain proportion, stir at 96±2℃ for 4-6 hours, and cool to obtain a polyvinyl alcohol aqueous solution; (3) Dissolution of protein: Dissolve the protein in a certain amount of water, stir at 50-60°C for 1-2 h, and cool to obtain a protein aqueous solution; (4) Preparation of spinning solution: The above-mentioned polyvinyl alcohol aqueous solution and protein aqueous solution are mixed at 60-80°C, and then the carboxylated graphene oxide solution is added. At the same time, an appropriate amount of a cross-linking agent, a flame retardant, an antibacterial agent and glycerol are added and stirred for about 2 h. The solution is filtered, allowed to stand, and degassed to finally obtain a uniform and stable spinning solution.

[0007] In the spinning solution obtained in the above steps, the polyvinyl alcohol content is 10% to 20%, the protein content is 0 to 10%, the cross-linking agent content is 0 to 5%, the flame retardant content is 1 to 10%, the antibacterial agent content is 0 to 1%, the carboxylated graphene oxide content is 0 to 1%, the water content is 50 to 90%, the glycerol content is 5 to 20%, and the total mass percentage of each component is 100%.

[0008] In the above steps, the cross-linking agent is a mixture of one or more of glutaraldehyde, aluminum chloride, sodium tetraborate, titanium oxide, and phytic acid.

[0009] In the above steps, the flame retardant is trioctyl phosphate, tricresyl phosphate or other series of flame retardants.

[0010] In the above steps, the antibacterial agent is nano-silver, nano-copper, nano-zinc, nano-oxide organic metal framework-loaded antibacterial agent or organic quaternary ammonium salt antibacterial agent.

[0011] In the above steps, the polyvinyl alcohol is selected from high alcoholysis degree products with a polymerization degree of more than 1700, such as 1799 type, 2199 type, 2499 type, etc. The protein is soy protein, keratin, milk protein, silk protein, etc.

[0012] Step 2 Spinning: The spinning solution prepared in step 1 is wet-spinned to prepare finished fibers, and the process flow is: spinning solution → extrusion in a coagulation bath → drawing → heat setting → acetalization treatment → washing → oiling → drying → finished product.

[0013] In the above steps, the coagulation bath is a saturated sodium sulfate aqueous solution, or an aqueous solution to which a certain amount of zinc sulfate is added, the temperature is 35-45° C., and the fiber residence time is 30-90 seconds.

[0014] In the above steps, the coagulation bath is a 280-420 g / L sodium sulfate water-glycerol solution, wherein the ratio of water to glycerol is 5:1 to 1:1.

[0015] In the above steps, the coagulation bath is a 280-420 g / L sodium sulfate aqueous solution, or an aqueous solution to which 10-60 g / L sodium hydroxide is added.

[0016] In the above steps, the heat stretching is performed at a ratio of 0.5 to 5.5 times, a heat setting temperature of 150 to 220° C., and a heat setting time of 3 to 5 minutes.

[0017] In the above steps, the acetalization composition is formaldehyde 25-50 g / L, sulfuric acid 160-200 g / L, sodium sulfate 120-180 g / L, the acetalization temperature is 60-80° C., and the time is 10-20 min.

[0018] In the above steps, the spinneret aperture is 0.4-0.7 mm, and the extrusion speed is 0.3 mL / min.

[0019] The present invention has the following advantages and beneficial effects:

[0020] 1. The present invention selects wet spinning, and the preparation process is simple, economical, and easy to implement in continuous industrial production.

[0021] 2. The polyvinyl alcohol regenerated protein fiber of the present invention has a smooth and soft surface and excellent strength, which effectively solves the problems of traditional chemical fiber distortion and low strength and modulus of natural polymer fibers.

[0022] 3. In the simulated hair of the present invention, glycerol is added to the spinning solution. Due to the action of glycerol and polyvinyl alcohol hydroxyl group, the prepared silk strips can be stretched to a higher multiple, the fiber mechanical properties are better, and the heat resistance is better. At the same time, graphene oxide is added, and the prepared simulated silk has a good drape and the luster of real hair.

[0023] 4. The present invention adds glycerol or sodium hydroxide to the coagulation liquid, thereby solving the problem that the fiber cross section forms a non-circular cross section due to the excessively fast forming speed. DETAILED DESCRIPTION

[0024] Although the present invention is described in the following examples, the present invention is not limited to these embodiments, and any improvements made by using the method concept and technical solution of the present invention are within the protection scope of the present invention.

[0025] Examples 1-4

[0026] The preparation process of Examples 1-4 is as follows, the only difference being: changing the stretching ratio in step 2 to 0.5, 1, 2, and 3 times; corresponding to Examples 1-4, respectively.

[0027] Prepare spinning solution: Prepare spinning solution: dissolve 6.3 g of PVA in 30 mL of water at 96°C and stir for 4 h until uniform; at the same time, dissolve 0.7 g of soy protein in 5 mL of water at 50°C and stir for 2 h until uniform; pour the soy protein solution into the PVA solution, control the temperature at 70°C and continue stirring, add 0.3% glutaraldehyde cross-linking agent, 2% trioctyl phosphate flame retardant, 1% nano-antibacterial agent, 0.1% carboxylated graphene oxide, and finally add 10 mL of glycerol to obtain a composite spinning solution.

[0028] Preparation of composite fibers: The composite spinning solution at 70°C was transferred to a syringe and extruded through a 0.7 mm spinneret into a saturated sodium sulfate coagulation bath at 45°C. The nascent fibers were obtained through double diffusion of the solution and water. The nascent fibers then entered the second coagulation bath to fully coagulate and form. The nascent fibers were then stretched 0.5-3 times in dry hot air and finally heat-set at 180°C for 3 min to obtain composite fibers.

[0029] The composite fibers with different stretching ratios were subjected to tensile tests (the mechanical properties of the fibers were tested at room temperature using a precision universal tensile testing machine with a stretching rate of 10 mm / min). The results are shown in Table 1.

[0030] Table 1 Mechanical properties of Examples 1-4 Example Stretching ratio Breaking strength (cN / dtex) Elongation at break (%) Young's modulus (cN / dtex) 1 0.5 1.12 56.20 72.2 2 1 1.50 46.36 76.6 3 2 2.45 34.02 83.0 4 3 3.04 29.93 92.7

[0031] During the stretching process of the fiber, the orientation and structural reconstruction of the macromolecules depend on the stretching multiple, which is also one of the important factors affecting the fiber strength. As can be seen from the table, with the increase of the stretching multiple, the fiber's breaking strength increases and the breaking elongation decreases. This is because the greater the stretching multiple, the greater the orientation and crystallinity of the fiber's macromolecular chains, so the higher the strength. Therefore, proper stretching of the primary fiber helps to improve the mechanical properties of the fiber.

[0032] Embodiment 5-8

[0033] The preparation process of Examples 5-8 is basically the same as that of Examples 1-4, except that the heat setting temperature in step 2 is changed. On the basis of a stretching ratio of 3 times and a heat setting time of 3 minutes, the heat setting temperature of 180°C is changed to 160°C, 170°C, 190°C, and 200°C, respectively corresponding to Examples 5-8. The results obtained are shown in Table 2.

[0034] Table 2 Mechanical properties of Examples 5-8 Example Heat setting temperature (℃) Breaking strength (cN / dtex) Elongation at break (%) Young's modulus (cN / dtex) 5 160 2.97 26.90 88.1 6 170 3.03 24.76 91.2 7 190 2.70 24.32 84.2 8 200 2.64 20.67 77.0

[0035] The strength of the heat-set fiber gradually increases with the increase of the heat-setting temperature. Compared with Example 4, it reaches the maximum at 180°C and then tends to decrease. This may be because the temperature is too high, causing the destruction rate of the fiber crystal region to be greater than the establishment rate. At the same time, the fiber surface will undergo oxidation degradation at this temperature, so the fiber strength decreases. Therefore, the appropriate heat-setting temperature is also the key to improving fiber performance.

[0036] Examples 9-12

[0037] The preparation process of Examples 9-12 is basically the same as that of Examples 1-4, except that the heat setting time in step 2 is changed. On the basis of a stretching ratio of 3 times and a heat setting temperature of 180°C, the heat setting time is changed to 1 min, 2 min, 4 min, and 5 min, respectively corresponding to Examples 9-12. The results obtained are shown in Table 3.

[0038] Table 3 Mechanical properties of Examples 9-12 Example Heat setting time (min) Breaking strength (cN / dtex) Elongation at break (%) Young's modulus (cN / dtex) 9 1 2.43 41.33 72.7 10 2 2.56 30.27 80.5 11 4 2.86 34.78 92.4 12 5 2.89 24.18 92.8

[0039] The breaking strength and modulus of the composite fiber gradually increased with the increase of heat setting time, and the breaking elongation gradually decreased, which was attributed to the fact that the heat setting time promoted the improvement of fiber crystallinity. At the same time, since too long heat setting time would cause oxidative degradation of the fiber surface, the fiber strength decreased slightly after heat setting for 3 minutes.

[0040] Examples 1-12 illustrate that the composite fiber prepared by stretching the primary fiber 3 times, heat setting at 180°C and heat setting for 3 min has the best performance, and then carboxylated graphene oxide (GO-COOH) is used to reinforce the composite fiber prepared under this condition.

[0041] Examples 13-17

[0042] The preparation process of carboxylated graphene oxide is as follows: 0.1 g of graphene oxide was weighed and added to 100 mL of deionized water to prepare 1 mg mL -1 The solution was uniformly dispersed by ultrasonication for 1 h. 6 g NaOH was added to the graphene oxide dispersion, and 5 g chloroacetic acid was added after stirring and dissolving. The mixed solution was ultrasonicated in a water bath at room temperature for 2 h for carboxylation reaction, and then taken out and stirred at room temperature overnight. Finally, it was centrifugally washed with deionized water and anhydrous ethanol for 3 times, and finally the product was dried in a vacuum oven at 30°C for 12 h to obtain carboxylated graphene oxide.

[0043] The preparation process of the spinning solution is basically the same as step 1, except that: the soybean protein solution is added to the PVA solution and stirred for 1-2 h, and then a certain mass fraction of carboxylated graphene oxide is added and stirred for 2 h to obtain a composite spinning solution.

[0044] The preparation process of the composite fibers of Examples 13-17 is basically the same as that of Examples 1-4, with a stretching ratio of 3 times, a heat setting time of 3 minutes, and a heat setting temperature of 180°C. The difference is that 0.1, 0.3, 0.5, 0.7, and 1 wt% of carboxylated graphene oxide are added to the spinning solution; they correspond to Examples 13-17, respectively. The results are shown in Table 4.

[0045] Table 4 Mechanical properties of Examples 13-17 Example Carboxylated graphene oxide mass fraction (wt%) Breaking strength (cN / dtex) Elongation at break (%) Young's modulus (cN / dtex) 13 0.1 3.04 29.42 89.74 14 0.3 3.19 33.60 104.20 15 0.5 3.29 32.58 113.92 16 0.7 2.89 28.92 86.23 17 1.0 2.74 27.82 78.88

[0046] The breaking strength and modulus of the composite fiber show a trend of first increasing and then decreasing with the addition amount of carboxylated graphene oxide. When the addition amount is 0.3wt%, the mechanical properties of the fiber are optimal. This is because, when the addition amount of carboxylated graphene oxide is small, the carboxylated graphene oxide is uniformly dispersed in the PVA matrix and there is high molecular entanglement and strong interface interaction between the two components; when the addition amount of carboxylated graphene oxide is large, the carboxylated graphene oxide cannot be better dispersed in the polymer matrix, and agglomeration occurs, resulting in defects in the composite fiber and a decrease in mechanical properties.

[0047] Compared with Example 4, the strength of the composite fibers in Examples 14-15 is increased, proving that low-load carboxylated graphene oxide has a significant reinforcing effect on polyvinyl alcohol / soy protein fibers.

[0048] Although the embodiments of the present invention have been shown and described above, the present invention is not limited to the above-mentioned manner. As long as various improvements are made using the method concept and technical solution of the present invention, they are all within the protection scope of the present invention.

Claims

1. A simulated hair and a preparation method thereof, comprising the following steps: Place polyvinyl alcohol in water at room temperature and stir for 1 to 2 hours to remove impurities such as sodium acetate and oligomers; mix the polyvinyl alcohol and distilled water in a certain proportion, stir at 96±2°C for 4-6 hours, and obtain a polyvinyl alcohol aqueous solution after cooling; dissolve the protein in a certain amount of water, stir at 50-60°C for 1-2 hours, and obtain a protein aqueous solution after cooling; blend the polyvinyl alcohol aqueous solution and the protein aqueous solution at 60-80°C, then add GO-COOH solution, and add appropriate amounts of cross-linking agent, flame retardant, antibacterial agent and glycerol and stir for about 2 hours, filter, stand and degas to obtain a spinning solution; prepare the spinning solution prepared above into finished fiber through stretching and other steps in a coagulation bath, and the process flow is: spinning solution→extrusion in coagulation bath→drawing→heat setting→acetalization treatment→washing→oiling→drying→finished product.

2. The method for preparing artificial hair according to claim 1, characterized in that: The polyvinyl alcohol content is 10-20%, the protein content is 1-10%, the cross-linking agent content is 0-5%, the flame retardant content is 1-10%, the antibacterial agent content is 0-1%, the carboxylated graphene oxide content is 0-1%, the water content is 50-90%, the glycerol content is 5-20%, and the total amount of each component is 100%.

3. The method for preparing artificial hair according to claim 1, characterized in that: The coagulation bath is a saturated sodium sulfate aqueous solution, or an aqueous solution to which a certain amount of zinc sulfate is added, the temperature is 35-45° C., and the fiber residence time is 30-90 seconds.

4. The method for preparing artificial hair according to claim 1, characterized in that: The heat setting heat stretching multiple is 0.5 to 3 times, the heat setting temperature is 150 to 220° C., and the heat setting time is 3 to 5 minutes.

5. The method for preparing artificial hair according to claim 1, characterized in that: In the extrusion in the coagulation bath, the spinneret aperture was 0.4-0.7 mm and the extrusion speed was 0.3 mL / min.

6. The method for preparing artificial hair according to claim 2, characterized in that: The cross-linking agent is one or more of glutaraldehyde, aluminum chloride, sodium tetraborate and titanium oxide.

7. The method for preparing artificial hair according to claim 2, characterized in that: The flame retardant is trioctyl phosphate, tricresyl phosphate or other series of flame retardants.

8. The method for preparing artificial hair according to claim 2, characterized in that: The antibacterial agent is nano silver, nano copper, nano zinc, nano oxide or organic quaternary ammonium salt antibacterial agent.

9. The method for preparing artificial hair according to claim 2, characterized in that: Polyvinyl alcohol can select high alcoholysis degree products with a polymerization degree of more than 1700, such as type 1799, type 2199, type 2499, etc.; the protein can be soy protein, keratin, milk protein, silk protein, etc.

10. The method for preparing artificial hair according to claim 2, characterized in that: In the acetalization treatment, the acetal solution comprises 25-50 g / L formaldehyde, 160-200 g / L sulfuric acid, and 120-180 g / L sodium sulfate, and the acetalization temperature is 60-80° C. and the time is 10-20 min.

Citation Information

Patent Citations

  • Method for preparing collagen / polyvinyl alcohol composite fiber using dialdehyde as cross-linking agent

    CN101008110A

  • Preparation method of collagen fiber for artificial hair

    CN101597817A

  • Method for preparing protein / polyving akohol composite fiber by utilizing polybasic carboxylic acid as cross linking agent

    CN102605461A

  • Graphene-compounded PVA (polyvinyl alcohol) master batch with high performance, application and fiber material

    CN106832399A

  • Graphene oxide modified polyvinyl alcohol film, and preparation and application thereof

    CN109553787A